Technique for rerouting without traffic disruption in optical networks. Issue 7 (1st March 2014) - Meloni, G.; Sambo, N.; Berrettini, G.; Cugini, F.; Potì, L.; Castoldi, P.
Abstract : A novel lightpath rerouting technique is proposed, allowing data lossless rerouting without requiring additional optical transponders. Data lossless rerouting effectiveness is demonstrated considering a 112 Gbit/s polarisation multiplexed quadrature phase shift keying lightpath and coherent receiver.